IMPLEMENTASI MESIN PENGURAI SABUT KELAPA UNTUK OPTIMALISASI PEMANFAATAN LIMBAH SABUT KELAPA MENJADI COCOPEAT DAN COCOFIBER GUNA MENDORONG PEREKONOMIAN DUSUN KARYA TANI DESA JERUJU BESAR - Imansyah, Fitri; Arsyad, Muhammad Iqbal; Sujana, Ivan (Jurnal Abdi Insani, 2024)
Coconut fiber waste is a significant source of environmental pollution in many areas, including in the Karya Tani hamlet, Jeruju Besar Village. To overcome this problem, community service activities are carried out with a focus on implementing coconut fiber decomposing machines to optimize the use of this waste. The main aim of this activity is to improve the local economy by utilizing coconut fiber waste into value-added products such as cocopeat and cocofiber. The implementation method involves training the community in the use of coconut fiber decomposing machines and the process of processing waste into cocopeat and cocofiber. The results of this activity show an increase in cocopeat and cocofiber production as well as an increase in income for local communities. Apart from that, using a coconut fiber decomposing machine also helps reduce the negative impact of coconut fiber waste on the environment. Evaluation of this activity identified several technical and logistical obstacles encountered, but overall, this activity was successful in providing significant economic benefits to local communities while reducing the negative environmental impacts of coconut fiber waste. In conclusion, collaboration between government, educational institutions and communities is essential in addressing environmental problems while improving local economic prosperity.